Free public library for Great Bend, Kansas - Spuhler, Henry Adam (My University, 1906)
Introduction: Specifications of material and labor required for the erection of a Library building to be built in Great Bend, Kansas, for the citizens thereof, who will be represented by a Library Board, or agent, transacting business and the building operation for them. Said Library is to be built according to plans, drawings, details and specifications prepared for same by Henry A. Spuhler, Architect, Manhattan, Kansas. These plans, etc., referred to herein, consist of the following drawings, all drawn to a scale of 1/8 inch to one foot, except where otherwise stated: No.1, Plate of front elevation, No.2, Plate of side elevation, No.3, Plan of basement, No .4, Plan of first floor, No.5, Plan of second floor, No.6, Longitudinal Section, No.7, Plate of side elevation, No.8, Plate of rear elevation, No.9, Plate of details of entablature, No .10, Plate of details for construction, No.11, Plate of details of roof truss and capital, No .12, Plate of details of interior finish and window frame. The drawings, together with these specifications and oral directions from the Architect or Superintendent, are intended to be sufficient for the necessary guidance to the furnishing of material to be used, and the required work to be done in the construction and completion of the aforesaid building.
Citation: Spuhler, Henry Adam. Free public library for Great Bend, Kansas. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Architecture; Public Library; Great Bend; Kansas; Building Specifications; Blueprints; Theses